(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Several factors conspired to weaken the Buyid state and undermine its power, thus disrupting its structure and taking away its glory and splendor. Where some Arab families took it upon themselves to fight and confront the Buyid family, and among those emirates that wrestled with the Buyid state, the Hamdanis who faced the Mu’izz of the state in two successive wars and then acquiesced to him and left them their rule in Mosul in return for the payment of royalties. The Buyihs, were it not for the fact that circumstances reversed them, and the Bani Mazyad in Hilla, who were moving in their loyalty between the leaders of the Buyihs and the Banu Shaheen in the deserts of Iraq, who resisted the Buyids for forty years until they disintegrated from within their family, and it was difficult for those Arab families and those who formed separate emirates to eliminate the Buyid state and getting rid of its influence in the territory of Iraq, but it played a role in undermining its power and draining its military energies in wars and therefore had a major role in limiting its power and distracting it from expansion.